2023
DOI: 10.3389/fmed.2022.1055252
|View full text |Cite
|
Sign up to set email alerts
|

Notoginsenoside Fc ameliorates renal tubular injury and mitochondrial damage in acetaminophen-induced acute kidney injury partly by regulating SIRT3/SOD2 pathway

Abstract: IntroductionMitochondria dysfunction is one of the primary causes of tubular injury in acute kidney injury (AKI). Notoginsenoside Fc (Fc), a new saponin isolated from Panax notoginseng, exhibited numerous pharmacological actions. However, the beneficial effects of Fc on renal tubular impairment and mitochondrial dysfunction in AKI have not been fully studied.MethodsIn this study, we established acetaminophen (APAP)-induced AKI model in mice to examine the therapeutic impacts of Fc on AKI.ResultsOur results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…This dramatic rise in creatinine and urea levels demonstrated, in this investigation, that APAP overdose-induced renal dysfunction and nephrotoxicity as nitrogen wastes in serum were in harmony with many studies that suggested increased oxidative stress and inflammation outputs as main and intermediate promoters. 2,55 In renal diseases, urea, and creatinine accumulate in serum not because of intensified production but because of a decreased clearance rate, indicating a defect in renal function. 56 Kidney damage from acetaminophen (APAP) toxicity involves multiple pathways.…”
Section: Discussionmentioning
confidence: 99%
“…This dramatic rise in creatinine and urea levels demonstrated, in this investigation, that APAP overdose-induced renal dysfunction and nephrotoxicity as nitrogen wastes in serum were in harmony with many studies that suggested increased oxidative stress and inflammation outputs as main and intermediate promoters. 2,55 In renal diseases, urea, and creatinine accumulate in serum not because of intensified production but because of a decreased clearance rate, indicating a defect in renal function. 56 Kidney damage from acetaminophen (APAP) toxicity involves multiple pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the distinct ginsenoside levels suggested that using ginsenosides alone could still be sufficient to classify PVV and PVF (Figure 6). Among the markers, OT-type saponins such as M-R2 and V-R2 have been known mainly for their anti-inflammatory effects [25], while other PPD-type saponins such as G-Rd, G-Rb1, G-Rb2, N-Fa, N-Fc and PPT-type saponins such as N-R1 have been reported with various pharmacological activities, including anti-amnestic and anti-aging [26], neuroprotective [27], reduction of renal tubular injury and mitochondrial dysfunction [28], anti-hyperlipidemic activities [29], anti-coagulation [30], etc. Usually, the differences in the metabolite composition of the herbal medicine are directly related to the differences in their clinical efficacy.…”
Section: Multivariate Analysis Of the Metabolome Differences Between ...mentioning
confidence: 99%
“…It was reported that it could attenuate HG-induced vascular endothelial cell injury, partly through the upregulation of PPARγ [5]. Fc might reduce renal tubular injury and mitochondrial dysfunction in AKI partly through the regulation of the SIRT3/SOD2 pathway [6]. Fc can accelerate reendothelialization and alleviate excessive neointimal formation following carotid artery injury in diabetic Sprague-Dawley rats in vivo [7].…”
Section: Introductionmentioning
confidence: 99%